Pengaruh Kinerja Keuangan, Kinerja Lingkungan, Umur Perusahaan dan Islamic Governance Score Terhadap Pengungkapan Islamic Social Reporting - Fadilla Freya Damayanti; Fatchan Achyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the influence of financial performance, environmental performance, company age, and Islamic Governance Score on the disclosure of Islamic Social Reporting (ISR). Islamic Social Reporting (ISR) is an index of corporate social responsibility disclosure based on Islamic principles. The population of this study comprises Islamic banking companies listed on the Financial Services Authority (OJK) during the 2019-2022 period. The sampling method used in this study is purposive sampling. The total sample used in this study is 10 Islamic banking companies. Data analysis is conducted using descriptive statistics and classical assumption tests, as well as hypothesis testing with multiple linear regression, Adjusted R2 test, F test, and t test. The results of this study indicate that environmental performance has a significant effect on ISR disclosure, while financial performance, company age, and Islamic Governance Score do not affect ISR disclosure